Pedoman Risiko, Struktur Risiko, dan Asesmen Risiko PT XYZ Tahun 2022-2023 - Prisidiyani, Nadetya Azzahra; Prasetyo, Aries Heru (Journal of Emerging Business Management and Entrepreneurship Studies, 2022)
PT XYZ is a multinational professional services company specializing in business management, information technology, and outsourcing. Implementing risk management considered less optimal is marked by the absence of a risk management role in the organization structure. These risk management guidelines are not under the ‘best practice’ and are followed by the presence of risks that often occur in the internal and external environment, indicating that it is necessary to carry out a risk assessment to reduce the impact of the risks arise. This qualitative research aims to determine guidelines, structures, and risk assessment of PT XYZ. This study identifies 21 corporate risks derived from four categories; strategic risk, financial risk, operational risk, and externality risk, with categories of four very high risks, eight high risks, four moderate risks, three low risks, and two very low risks. Based on the proposed risk treatment, there are two ways of risk treatment that PT XYZ can do, including risk reduction and risk acceptance. The risk treatment can be carried out as soon as possible to avoid and minimize the risks that may occur.